pengaruh disiplin kerja dan motivasi kerja terhadap kinerja pemanen afdeling 1 kebun melati ptpn4 regional 2 - Simangunsong, Steven Pranata; Purjianto, Purjianto (Lembaga Teewan Journal Solutions, 2026)
This study aims to determine the effect of work discipline and work motivation on harvester performance in Afdeling I Kebun Melati PTPN IV Regional II. The type of research used is associative research with a quantitative approach. The population in this study were all harvesters in Afdeling I Kebun Melati, totaling 27 people. The sampling technique used saturated sampling, so that the entire population became research respondents. Data processing used SPSS 25. The results showed that work discipline had a positive and significant effect on harvester performance with a calculated t value of 4.447> t table 1.711 and a significance of 0.000 <0.05. Work motivation also had a positive and significant effect on harvester performance with a calculated t value of 4.109> t table 1.711 and a significance of 0.000 <0.05. Simultaneously, work discipline and work motivation have a positive and significant effect on harvester performance, with a calculated F value of 58.300 > F table 3.40 and a significance level of 0.000 < 0.05. The coefficient of determination (R²) of 0.829 indicates that 82.9% of the variation in harvester performance can be explained by work discipline and work motivation, while the remaining 17.1% is influenced by other factors outside the study.